The Public Service - Planning Commission (Planning Commission, Government of India, 1953)
In his convocation address at the University of Travancore on December 18, 1953, Shri N. Raghavan Pillai emphasized the pivotal role of the Civil Service as a vocation dedicated to serving the community through effective and ethical administration. Addressing both the historical shortcomings and future responsibilities of civil servants, he highlighted the urgent need for integrity, efficiency, and team spirit, particularly in the context of India’s transition toward a modern Welfare State. Pillai argued for a reorientation of civil servants’ mindset from rigid professionalism to an engaged, service-oriented approach, encouraging active involvement in social and economic development while maintaining impartiality. He stressed the importance of character development alongside academic competence, advocating discipline, non-attachment, and collaborative effort as essential qualities for public leadership. Addressing graduating students, he underscored their responsibility to contribute to national development, particularly through the successful implementation of the Five-Year Plan and initiatives that uplift marginalized communities. The address concluded with a message of optimism and purpose, calling on graduates to embrace service to society as the guiding principle of their careers, reflecting a vision of a Civil Service committed to ethical governance, social progress, and national development.
Address delivered at the Nineteenth Convocation of the University of Travancore on December 18, 1953 Government of India Planning Commission
Address delivered at the Nineteenth Convocation of the University of Travancore on December 18, 1953 Government of India Planning Commission
Keywords: Civil Service; Shri N. Raghavan Pillai; Welfare State; Public Administration; Integrity; Efficiency; Team Spirit; Character Development; Five-Year Plan; Social Responsibility; National Duty; Community Service